Silica Synthesis from Mount Semeru Volcanic Ash as a Nickel Heavy Metal Adsorbent - Darmawan, Raden; Juliastuti, Sri Rachmania; Hardiatmoko, Bagas; Defriana, Aulia; Laily, Fitria Nur (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
This study aims to synthesize SiO2 gel-based adsorbents using the sol-gel method from Mount Semeru volcanic ash through varying concentrations of sodium hydroxide and acid catalysts and to determine its adsorption capacity on nickel (Ni(II)). Volcanic ash was obtained from Lumajang District, East Java, Indonesia. The silica gel adsorbent was made using the sol-gel method with different amounts of NaOH (1.0 M, 2.0 M, 3.0 M, and 4.0 M) and acid catalysts (acetic and hydrochloric acid). First, silica (SiO2) was extracted from the volcanic ash, and then the sol-gel process was used to manufacture SiO2 gel-based adsorbents. The SiO2 gel was analyzed using X-ray Fluorescence Analysis, Fourier-transform Infrared (FTIR), and Brunauer Emmett, and Teller (BET). Adsorption analysis of the Ni(II) metal ion content was conducted at various stirring rates and adsorbent dose masses. The results obtained showed that the most optimal SiO2 gel was achieved when using 3.0 M NaOH, 10.53% HCl, and 8.30% CH3COOH. Through FTIR analysis, NaOH 3.0 M x HCl silica contains only the siloxane groups, whereas NaOH 3.0 M x CH3COOH silica contains both the silanol and siloxane groups. The best results were gained with SiO2-based adsorbents (NaOH 3.0 M x CH3COOH) at a dose of 10 g/L and a stirring rate of 50 rpm, with Ni(II) adsorption effectiveness of 99.80%. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).